(untitled) (Research, Society and Development, 2021)
In this work Bi1−xNdxFe0.99Co0.01O3 ceramics compositions were synthesized for x = 0.05, 0.20 and, y = 0.01. Structural refinement results show that most of the samples crystallized in a rhombohedral symmetry with R3c. Measurements magnetoelectric coefficient, show that the magnetoelectric coefficients are of second order. The electrical impedance characterization of in function external magnetic fields, has a relative variation of the real dielectric response, the loss tangent and the electrical impedance. The systems, as the DC magnetic field strength increased a gain in both the values of the dielectric constant variation, as well as the variation of the electrical impedance. In other words, the greater the intensity of the magnetic field, the greater your response. There were also significant variations with of the magnetic field AC.